Quantitative analysis for management - Bonini, Charles P.; Hausman, Warren H.; Bierman, Harold (Irwin, 1997)
Intended for use in an elective quantitative analysis course at the Junior level or first year MBA and in Modeling and Analysis, Decision Sciences or Management Science course. This text uses the Excel spreadsheet throughout. It includes Model building, Mathematical Programming, Simulation, and other spreadsheet applications.